DECREASEMENT OF LYSOPHOSPHATIDYLCHOLINE LEVEL, NF-KB EXPRESSION, INTIMA MEDIA THICKNESS AND IMPROVEMENT OF INSULIN RESISTANCE BY DARAPLADIB TREATMENT: IN VIVO STUDIES OF TYPE 2 DIABETES MELLITUS SPRAGUE-DAWLEY RAT MODEL - Wihastuti, Titin Andri; Andiyani, Dinda Zahra Putri; Andarini, Sri; Heriansyah, Teuku (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Lipoprotein-associated phospholipase A2 (Lp-PLA2) is an enzyme with several pro-inflammatory properties that involved in pathogenesis of atherosclerosis, but some investigation shows controversial views regarding its biological role. We examined the effect of selective inhibitor of Lp-PLA2 (darapladib) to the inflammation marker, intima-media thickness (IMT), and insulin resistance (IR) of type 2 diabetes mellitus (T2DM) rat model. This study aimed to measure lysophosphatidylcholine (lyso-PC) in serum and aortic tissue, nuclear factor kappa B (NF-κB) expression, IMT, and IR with darapladib treatment in a T2DM rat model. Methods: 30 Sprague-Dawley rats were randomly divided into normal group, T2DM group and T2DM with darapladib treatment. Induction of T2DM was done by giving high-fat diet and low dose injection of streptozotocin. Blood glucose level and insulin plasma concentration were measured to calculate IR. 8 weeks and 16 weeks after treatment, we compared lyso-PC level, NF-κB expression, and IMT. Results: Darapladib significantly decreased lyso-PC level, NF-κB expression, and IMT at two serial treatments. Darapladib treatment group exhibited significant reduction of IR (0.64±0.11 vs. 2.07±0.16, at 8 weeks; and 0.93±0.08 vs. 6.48±0.55 at 16 weeks) compared with T2DM group. Conclusions: These data suggested that Lp-PLA2 played a role in inflammation process, atherosclerosis, and IR occurring in metabolic disorder.